Crop growth and development of cucumber (Cucumis sativus L.) in Humocaro bajo, Lara State, Venezuela - Marcano, Carmen; Acevedo, Ingrid; Contreras, Jorge; Jiménez, Odalis; Escalona, Argelia; Pérez, Pablo (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to evaluate the crop growth and development of cucumber (Cucucmis sativus L.) in the horticultural zone of Humocaro, Lara state, three sites were selected, Sabaneta, Las Canoítas and La Estancia at 900, 110 and 840 meters above sea level, respectively, in the parish Humocaro Bajo, municipality Moran, Lara state. It was used a completely randomized design with three treatments and 20 replications. It was quantified the number of leaves, tendrils, flowers and fruits of leaves per plant during the crop growth and development of cucumber. It was found that the growth of cucumber plant according to the localities Sabaneta, Las Canoítas and La Estancia were similar (p> 0.05) in terms of plant height, number of leaves and tendrils into the seventh week, although it was found higher cucumber plant height (10.55 cm) in the town of Las Canoítas in the third week, and the largest number of leaves in the fourth and fifth week (12 to 13 and 16 to 18, respectively) at La Estancia and Las Canoítas. The number and length of the fruit was the same in the localities. However, there was greater diameter and fresh weight of fruit in the town of Las Canoítas. It was concluded that there was no apparent effect of the towns on the growth of cucumber plants, but not on yield components, ref lected in the diameter and fresh biomass of fruit in the cucumber plants developed in the town of Las Canoítas.
Keywords: Cucucmis sativus L.; growth; locality